The influence of gestational diabetes mellitus on the developing baby - Świątoniowska, Natalia Alicja; Rozensztrauch, Anna (Journal of Education, Health and Sport, 2017)
Gestational diabetes mellitus involves about 10% of women in Poland. The consequences of untreated gestational diabetes mellitus are seen in the prenatal development. The nursing care for the diabetes mother's newborns should be started in the moment of diagnosing. The treatment adherence of pregnant diabetic women gives a chances for having healthy baby and has an influence on the pregnancy, deliver and further baby growth.